Effect of modifier elements on machinability of AL-20%Mg2Si metal matrix composite during dry turning - Mohd. Yusof, Noordin (Taylor & Francis Inc, 2016)
The principle aim of this study was to observe the effect of machining parameters as well as the separate additions of 0.4 wt% bismuth, 0.01 wt% strontium, and 0.8 wt% antimony on the machinability of Al-20%Mg2Si in situ metal matrix composite. Microstructure alteration, surface roughness, main cutting force, and chip morphology were taken into account as indices to examine the effect of modifiers and machinability during dry turning. It was found that the additives modify the Mg2SiP particles by changing the particle shape from coarse primary to polygonal shape and decrease the particle size and aspect ratio as well as increase the particle density. Results show that the modified work-pieces present adequate machinability with respect to cutting force and surface roughness. The smaller reinforcements enable lower surface roughness values to be obtained even if they are pulled out, fractured, or elongated. In addition, the modified work-pieces encourage lower surface roughness values in comparison with unmodified work-piece due to less built-up-edge formation. A scenario for surface roughness of Al-Mg2Si composite with respect to the size and aspect ratio of reinforcement particles is proposed in this study.